2015
DOI: 10.1002/pssa.201532367
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial single‐crystal of GaSe epilayers grown on a c‐sapphire substrate by molecular beam epitaxy

Abstract: In this study, hetero-epitaxy of GaSe epilayers on a c-sapphire substrate achieved using molecular beam epitaxy was demonstrated. The GaSe epitaxial growth was monitored using in situ reflection high-energy electron diffraction (RHEED). Streak RHEED patterns showed a flat and highly crystalline situation. Furthermore, two RHEED patterns were observed after 15 min of growth, and they were correlated with the m-axis and a-axis of hexagonal GaSe. The single crystal of GaSe was verified using X-ray diffraction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…Since the positions of the new streaks compared with those of the Ge(111) streaks are consistent with the lattice constant difference between GaSe(0001) and Ge(111), which are 3.75 Å and 4.00 Å, respectively, it indicates that the GaSe thin film is growing on Ge(111) with the epitaxial relationship GaSe(0001) // Ge (111) and GaSe [11][12][13][14][15][16][17][18][19][20] // Ge [1][2][3][4][5][6][7][8][9][10]. As the growth proceeds, the Ge(111)-(1 × 1) streaks fade out and, in contrast, the GaSe(0001)-(1 × 1) streaks gradually become clearer and sharper ( Figure 1D).…”
Section: Rheedsupporting
confidence: 54%
See 4 more Smart Citations
“…Since the positions of the new streaks compared with those of the Ge(111) streaks are consistent with the lattice constant difference between GaSe(0001) and Ge(111), which are 3.75 Å and 4.00 Å, respectively, it indicates that the GaSe thin film is growing on Ge(111) with the epitaxial relationship GaSe(0001) // Ge (111) and GaSe [11][12][13][14][15][16][17][18][19][20] // Ge [1][2][3][4][5][6][7][8][9][10]. As the growth proceeds, the Ge(111)-(1 × 1) streaks fade out and, in contrast, the GaSe(0001)-(1 × 1) streaks gradually become clearer and sharper ( Figure 1D).…”
Section: Rheedsupporting
confidence: 54%
“…We investigated the growth of GaSe on Ge(111) by MBE and determined the atomistic structure of the thin film near the interface using HAADF-STEM and EELS. It was revealed that GaSe thin films can be grown on Ge(111) with GaSe(0001) // Ge(111) and GaSe [11][12][13][14][15][16][17][18][19][20] // Ge [1][2][3][4][5][6][7][8][9][10], and the Ge(111) surface is terminated by a half GaSe monolayer, on which the GaSe thin film is grown through vdWE. The grown layers adopt predominantly the expected wurtzite-like structure but monolayers with a zinc blende-like structure are locally observed near the film-substrate interface, which has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations